Unexpected rearrangements and a novel synthesis of 1,1-dichloro-1-alkenones from 1,1,1-trifluoroalkanones with aluminium trichloride - Lansbergen, Beatrice; Meister, Catherine S.; McLeod, Michael C. (Beilstein Journal of Organic Chemistry, 2021)
A novel reactivity of 1,1,1-trifluoroalkanones is reported, where the reaction with AlCl3 results in the formation of 1,1-dichloro-1-alkenones. The reaction scope was found to be broad, with various chain lengths and aryl substituents tolerated. For substrates containing an electron-rich aromatic ring, further reactions take place, resulting in bicyclic and/or rearrangement products.
Keywords: aluminium trichloride; dichloroalkenes; Friedel–Crafts alkylation; rearrangement; trifluoroalkanes